Jakościowe aspekty doskonalenia zarządzania organizacją: Qualitative aspects of the improvement of the organization’s management - Skrzypek, Adam (Management and Administration Journal, 2021)
Improvement of management systems has become a necessity in a changing environment conditions and in the light of growing demands and expectations of customers. Doing improvements to an organization is a process that is used in many areas of the organization’s operations and activities of employees. Improving management with redard to quality, knowledge, information, processes and consequently leads to improved efficiency and competitiveness of an organization. Improvement pro-cess should be integral and integrated. It is in the princilples of TQM philosophy where the links between doing improvements and management process excellence are clearly visible. A proven method for doing improvements to the management process is E. Deming’s PDCA cycle. The quest for excellence and improvement is often started by use of proven management models.